Quantifying the Aging of Lithium-Ion Pouch Cells Using Pressure Sensors - Yousof Nayfeh; Jon C. Vittitoe; Xianglin Li (Batteries)
Understanding the behavior of pressure increases in lithium-ion (Li-ion) cells is essential for prolonging the lifespan of Li-ion battery cells and minimizing the safety risks associated with cell aging. This work investigates the effects of C-rates and temperature on pressure behavior in commercial lithium cobalt oxide (LCO)/graphite pouch cells. The battery is volumetrically constrained, and the mechanical pressure response is measured using a force gauge as the battery is cycled. The effect of the C-rate (1C, 2C, and 3C) and ambient temperature (10 °C, 25 °C, and 40 °C) on the increase in battery pressure is investigated. By analyzing the change in the minimum, maximum, and pressure difference per cycle, we identify and discuss the effects of different factors (i.e., SEI layer damage, electrolyte decomposition, lithium plating) on the pressure behavior. Operating at high C-rates or low temperatures rapidly increases the residual pressure as the battery is cycled. The results suggest that lithium plating is predominantly responsible for battery expansion and pressure increase during the cycle aging of Li-ion cells rather than electrolyte decomposition. Electrochemical impedance spectroscopy (EIS) measurements can support our conclusions. Postmortem analysis of the aged cells was performed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) to confirm the occurrence of lithium plating and film growth on the anodes of the aged cells. This study demonstrates that pressure measurements can provide insights into the aging mechanisms of Li-ion batteries and can be used as a reliable predictor of battery degradation.